Mechanical properties and water absorption of kenaf/pineapple leaf fiber-reinforced polypropylene hybrid composites - Ng, Lin Feng; Dhar Malingam, Sivakumar; Razali, Nadlene; Chen, Wei Ping (John Wiley and Sons Inc., 2020)
Hybrid composites have shown innumerable benefits to the research communities in terms of environmental friendliness and mechanical properties. This research study presents the mechanical characterization and moisture uptake of kenaf/pineapple leaf fiber-reinforced polypropylene hybrid composites with several relative fiber ratios. A comparison was also made between nonhybrid and hybrid kenaf/pineapple leaf fiber-reinforced composites to investigate the hybridization effect. In this work, the composite materials were fabricated via the hot compression technique. Mechanical tests were performed to obtain the tensile, flexural, and Charpy impact properties of nonhybrid and hybrid kenaf/pineapple leaf fiber-based composites. The water absorption characteristics were then obtained by immersing the composite materials in the water until the saturation point was reached. The findings concluded that the mechanical properties and moisture uptake behaviors of the composites were improved through the hybridization. The hybrid composites with a relative fiber ratio of 25:75 were particularly promising with the improvement of 10.90% in tensile strength; 16.13% in flexural strength; and 6.80% in impact strength in both flatwise and edgewise orientations compared to nonhybrid kenaf-based composites. Meanwhile, the diffusion coefficient of hybrid composites (25:75) was 56.12% lower than nonhybrid pineapple leaf fiber-based composites. Thus, the results indeed demonstrated that the balance between mechanical properties and moisture sensitivity can be obtained through the hybridization of kenaf and pineapple leaf fiber in the composite materials.